The impact of access prices on train traffic: An econometric study for France. (December 2022) - Olarte-Bacares, Carlos Augusto; Brunel, Julien; Sigaud, Damien
Graphical abstract: Highlights: Moderate and negative impact of track access charges on High-Speed trains traffic. High and negative impact of track access charges on freight trains traffic. The impact of track access charges on regional trains traffic under PSO depends on the French pricing categories. The impact of track access charges on the demand of rail paths less used by regional trains is negative and statistically significant. Abstract: To guarantee fair and nondiscriminatory access to rail networks, European Commission raised the importance of regulation by promoting short run marginal cost. Thus, to recover the full cost of infrastructure, Infrastructure Managers may use mark ups over the marginal cost, using Ramsey pricing for example. However, a Ramsey pricing implementation for rail infrastructure is strongly limited by the lack of information about the demand elasticity of train paths. The aim of this article is to try to fill this gap by conducting an empirical research on the price sensitivity of the railway paths using a French dataset from 2003 to 2016. Preliminary results suggest that track access charges influence negatively the train path demand for high-speed trains and freight trains but do not seem to influence the train path demand for regional trains under PSO. Nevertheless, if track access charges are related to the track category (UIC category) or to the kind of line (high speed or conventional) results may differ. Regarding regional and freight trains, the track category seems to determine the statistical significance of track access charges elasticity while the kind of line seems to explain the impacts on the demand of rail paths for high-speed trains.